The impact of financial benefits on employee productivity: A case study of the joint clinical research centre in Lango Region, Northern Uganda - Robinah, Adong Mercy; Akello, Judith Abal (International Journal of Social Sciences Perspectives, 2023)
This study investigates the impact of financial advantages on staff productivity within the Joint Clinical Research Centre. It aims to explain the relationship between financial benefits and employee performance, highlighting their significance in enhancing engagement. Employing a mixed-methods approach, this research combines quantitative data gathered through a structured questionnaire with qualitative insights derived from interviews. The study utilizes cross-sectional survey methodology, sampling 142 participants, including team leaders and various staff categories affiliated with the Joint Clinical Research program. Data analysis involves descriptive statistics, correlation analysis, and regression analysis for quantitative data and content analysis for qualitative data. The study reveals a significant positive correlation between financial benefits and employee productivity, indicating that adequate financial incentives motivate employees to perform better. Regression analysis demonstrates that financial benefits can explain approximately 40.9% of the variability in employee productivity. The t-test results confirm a statistically significant association between financial benefits and employee productivity, rejecting the null hypothesis. Qualitative findings from key informants corroborate the importance of financial incentives in motivating employees and improving productivity. The study underscores the vital role of financial incentives in improving employee engagement and performance. Organizations, particularly in healthcare research, can leverage these insights to design strategies that enhance staff motivation, ultimately leading to increased productivity and better healthcare outcomes.